The Protective Effect of Sulforaphane on Dextran Sulfate Sodium-Induced Colitis Depends on Gut Microbial and Nrf2-Related Mechanism - Canxia He; Canxia He; Mingfei Gao; Xiaohong Zhang; Peng Lei; Haitao Yang; Yanping Qing; Lina Zhang (Frontiers in Nutrition, 2022)
Sulforaphane (SFN), an isothiocyanate present in cruciferous vegetables such as broccoli and brussels sprouts, has a variety of biological functions. This study was undertaken to assess the potential efficacy of SFN in ameliorating dextran sulfate sodium (DSS)-induced ulcerative colitis (UC) in mice and to elucidate the underlying mechanisms. UC was induced in mice with administration of 2% DSS in drinking water for 7 days. Male C57BL/6 mice were treated with Mesalazine (50 and 100 mg/kg body weight) and various doses of SFN (2.5, 5, 10, and 20 mg/kg body weight). In DSS colitis mice, the hallmarks of disease observed as shortened colon lengths, increased disease activity index (DAI) scores and pathological damage, higher proinflammatory cytokines and decreased expression of tight junction proteins, were alleviated by SFN treatment. SFN also partially restored the perturbed gut microbiota composition and increased production of volatile fatty acids (especially caproic acid) induced by DSS administration. The heatmap correlation analysis indicated that Lactobacillus johnsonii, Bacteroides acidifaciens, unclassified Rikenellaceae RC9, and unclassified Bacteroides were significantly correlated with disease severity. Nuclear factor (erythroid-derived 2)-like 2 (Nrf2), Signal Transducer and Activator of Transcription 3 (STAT3), and Phase II enzyme UDP-glucuronosyltransferase (UGT) were involved in the protective effect of SFN against DSS-induced colitis. This study's findings suggest that SFN may serve as a therapeutic agent protecting against UC.